SEKOLAH BERBASIS KECERDASAN MAJEMUK DI GRESIK - Saiul Anah (Al-Fakkaar, 2022)
Building school at essence is building excellence in human resources. Unfortunately, many school, consciously or not, actually kill a lot of the potential of their students. This research is a multi-intelligence-based school because there are many schools, especially in Surabaya, which are predicated as robot schools; starting from the learning process, school success, to the assessment system. Multiple intelligence-based schools are schools that value various types of student intelligence. In this study, it produces special moments, special moments, the theory of multiple intelligences, indicators of the best school being the best process and not the best input.